The Usage of Taboo Words in Dave Chappelle's The Closer Stand-Up Comedy - Hizkia Richard Sabathon Sihombing; Ni Luh Putu Krisnawati; Luh Putu Laksminy (Jurnal Langua, 2023)
Taboo words are the primary notion in this study. There are two objectives of this study, which are to classify the types of taboo words in the show and categorize their functions. The analysis was conducted based on the theories proposed by Battistela (2005) and Wardaugh (2005). Battistela (2005) differentiated taboo words into 4 categories; Epithets, Profanity, Vulgarity, and Obscenity. Wardaugh (2006) formulated the function of taboo words into four types: to draw attention to oneself, to show contempt, to be aggressive or provocative, and to mock authority The analyzed data taken from a comedy show Dave Chappelle’s The Closer Stand-up Comedy. The collected data is analyzed by using the descriptive qualitative method since it did not involve any numerical data. Through the analysis, the use of taboo terms in a speech is revealed; it helps the speaker deliver his points despite its rude and barbaric connotations. The comedy performance that mostly criticizes racial and LGBTQ+ phenomenon in America stimulates the speaker to use epithets as a tool for labeling the community member and making jokes. Through this comical performance, it can be concluded that taboo words can convey satire and critics to the current society, which the speaker considered as judgemental yet biased and unmerciful towards comedians. For this reason, it can be concluded that the use of taboo terms in a speech can help the speaker deliver his points despite their rude and barbaric connotations.